Perspectivas e propostas de inserção de bioquerosene de aviação no transporte aéreo de passageiros no Brasil - Roitman, Tamar (2018)
The global aviation industry has emitted 859 million tons of CO2, around 2% of all human-induced CO2 emissions, in 2017. Sector associations have set ambitious targets to face the challenges posed by climate change, and in order to achieve them, a basket of measures has been identified, which include aircraft-related technology development, alternative fuels, improving of air traffic management and infrastructure use, and marketbased measures. Sustainable aviation fuels present an opportunity to reduce aviation CO2 emissions without restricting demand, and Brazil has the potential to be a high-level producer of this biofuel. Amongst constraints for the creation of a biokerosene industry in Brazil, we can mention the feedstock availability and the need for a supply chain establishment, and the high production costs and investments involved, especially in the industry initial development phase. Besides that, airline companies are in a struggling position in Brazil, since they have operated with negative profit margins from 2011 to 2016. Fuels costs are the main cost element in the airline operational costs and any increase reflects directly in the airlines’ financial results. In this sense, the development of a SAF industry relies on political measures. In this work, five policy instruments suggestions for the introduction of biokerosene in air transport in Brazil were prepared, focusing in the development of a, aviation biofuel industry in Brazil.